Analisis Respon Agronomis Jagung (Zea mays L.) terhadap Variasi Dosis Pupuk NPK pada Sistem Tumpangsari untuk Optimalisasi Pertumbuhan dan Produktivitas - Pirhat, Nadiya (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Maize (Zea mays L.) is a strategic food commodity in Indonesia, playing a crucial role in national food security as the second most important source of carbohydrates after rice, as well as serving as an essential raw material for the livestock feed industry and various agro-industrial sectors. The increasing demand for maize underscores the need for land intensification strategies, particularly in cultivation areas with spatial limitations such as intercropping systems. However, the success of intercropping is highly dependent on nutrient availability to improve the physical, chemical, and biological properties of the soil, thereby enhancing nutrient use efficiency. In this context, the present study aimed to evaluate the effects of NPK fertilizer application on the growth and productivity of maize under an intercropping system, in order to establish a scientific basis for effective, efficient, and sustainable fertilization recommendations. The experiment was conducted at the Dharmasraya Campus III Experimental Farm, Andalas University, from August to December 2025. The study employed a factorial experiment arranged in a Split Plot Design with two factors. The first factor consisted of two cropping systems: monoculture and polyculture, while the second factor comprised three NPK Mutiara 16-16-16 fertilizer rates: 150 kg ha⁻¹, 250 kg ha⁻¹, and 350 kg ha⁻¹. Each treatment combination was replicated three times, resulting in a total of 18 experimental plots. Observed parameters included vegetative growth variables—plant height (cm) and number of leaves at 28, 35, and 42 days after planting (DAP)—as well as generative variables—ear weight with husk (g), ear weight without husk (g), ear length with husk (cm), and ear length without husk (cm). Results indicated that the application of NPK at a rate of 350 kg ha⁻¹ (sub-plot treatment P3) produced a significant agronomic response, optimizing various growth parameters in both vegetative and generative phases. Based on these findings, a recommended practice is the application of 350 kg ha⁻¹ NPK fertilizer in three split doses at 7 DAP, 28 DAP, and 42 DAP, prior to the generative phase, to support ear development and yield potential. Further research is recommended to investigate the interaction of 350 kg ha⁻¹ NPK application with variations in plant spacing, maize varieties, and diverse agro-climatic conditions, in order to validate these results and refine fertilization recommendations for broader adoption in intercropping systems